2015
DOI: 10.1128/jvi.01499-15
|View full text |Cite
|
Sign up to set email alerts
|

A Novel PDZ Domain Interaction Mediates the Binding between Human Papillomavirus 16 L2 and Sorting Nexin 27 and Modulates Virion Trafficking

Abstract: Previous studies have demonstrated an interaction between sorting nexin 17 and the L2 capsid proteins from a variety of papillomavirus types. This interaction is required for late endosomal trafficking of the L2 protein and entry of the L2/DNA complex into the nucleus during infection. Here we show an interaction between papillomavirus L2 proteins and the related PX-FERM family member sorting nexin 27 (SNX27), which is mediated in part by a novel interaction between the PDZ domain of SNX27 and sequences in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 31 publications
2
67
0
1
Order By: Relevance
“…(ii) The L2 protein may even span the TGN membrane twice, whereas both the N and C termini and the viral genome reside in the lumen during trafficking. Theoretically, this would allow for the L2 protein to interact with its cytosolic binding partners needed for intracellular trafficking preceding true translocation of the L2/DNA complex (29)(30)(31)(33)(34)(35)(36)(37), while at the same time allowing the carboxyl-terminal putative DNA binding domain on the luminal side to interact with viral genome. However, at the onset of mitosis, the carboxyl terminus has been shown by the Campos group to be accessible in the cytosol, suggesting that at this time the L2 protein assumes the possible type I transmembrane configuration previously suggested by us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) The L2 protein may even span the TGN membrane twice, whereas both the N and C termini and the viral genome reside in the lumen during trafficking. Theoretically, this would allow for the L2 protein to interact with its cytosolic binding partners needed for intracellular trafficking preceding true translocation of the L2/DNA complex (29)(30)(31)(33)(34)(35)(36)(37), while at the same time allowing the carboxyl-terminal putative DNA binding domain on the luminal side to interact with viral genome. However, at the onset of mitosis, the carboxyl terminus has been shown by the Campos group to be accessible in the cytosol, suggesting that at this time the L2 protein assumes the possible type I transmembrane configuration previously suggested by us.…”
Section: Discussionmentioning
confidence: 99%
“…During this time, data suggest that the L2 protein undergoes conformational changes resulting in translocation of the majority of the protein across the endosomal membrane through possible solo or concerted efforts of a membrane-destabilizing (residues 445 to 467) and a transmembrane-like (residues 45 to 65) domain (26)(27)(28)(29). This translocation event allows for the cytoplasmic region of the L2 protein (likely residues 65 to 473) to directly interact with cytoplasmic factors, most notably, the retromer complex, which facilitates the trafficking of the L2/DNA complex to the trans-Golgi network (TGN) (29)(30)(31)(32)(33)(34)(35)(36)(37). Residues 13 to 45 are located on the luminal side of transport vesicles, whereas residues 45 through 65 span the membrane.…”
mentioning
confidence: 99%
“…The transit of vesicles to the TGN and nuclear entry probably involves movement along microtubules by way of molecular motors, since L2 has been shown to interact with dynein [25], while a membrane-associated cellular protease g-secretase is required for localization of L2 and viral DNA to the Golgi apparatus and endoplasmic reticulum [17,26]. It is becoming clear that extensive cellular cargo sorting machinery is involved in L2-related HPV trafficking from endosomes to the nucleus, including SNX17 [21] and SNX27 [27], retromer proteins [23], and at least one member of the ESCRT complex, TSG101 [28]. The exact sequence of events in which HPVs utilize members of the host sorting machinery for the transition to TGN and nucleus remains an important question.…”
Section: Introductionmentioning
confidence: 99%
“…SNX17 is localized in early endosomes and recycling tubules and is primarily involved in endosomal recycling of transmembrane proteins, including the lowdensity lipoprotein receptor (LDLR) family [32,33] and b1 integrins [34], among others. The related protein SNX27 shares several structural features with SNX17 and also binds to L2 proteins [27]. Both proteins belong to a subfamily of PX-FERM endosomal membrane scaffolds [31], but SNX27 also has an amino-terminal PDZ domain through which it targets a different repertoire of cargoes.…”
Section: Introductionmentioning
confidence: 99%
“…DiGiuseppe and coworkers revealed that L2 amino acid residues 64 to 81 and 163 to 170 and the L2 C-terminal exposure on the cytosolic side of intracellular membranes enable interaction with cytosolic host cell factors (39). Interactions of L2 with actin (40), components of the retrograde transport machinery (37,41,42), sorting nexins 17 and 27, TSG101, ␥-secretase, and Hsc70, as well as the microtubule network, have been reported (37,(41)(42)(43)(44)(45)(46)(47)(48). These interactions result in trafficking to the Golgi network (37,41,42,47), transport toward the nucleus (43,44), and accumulation at nuclear substructures (49)(50)(51)(52)(53).…”
mentioning
confidence: 99%